Look i'm happy : copy the faces to learn about feelings - Italiano, Lee; Kealy, Rebecca; Passchier, Andy (Cottage Farm, UK Autumn Publishing, 2023)
Can you make a happy face? Or look surprised? Look in the mirror and do your best funny faces in this clever learning book about feelings
Hobbies
Keywords: Hobbies